THE IMPACT OF THE COMPANY’S LIFE CYCLE ON THE ACCOUNTING CONSERVATISM AND ITS REFLECTION ON THE ECONOMIC DECISIONS OF INVESTORS / A STUDY IN A SAMPLE OF IRAQI BANKS LISTED IN THE IRAQI STOCK EXCHANGE (World Economics and Finance Bulletin, 2022)
The current research aimed to analyze the intellectual and applied impact in each of the life stages of the company in both the accounting conservatism and the economic decisions of investors, by applying to 130 views (company / year) in the Iraqi banks listed in the Iraq Stock Exchange for the period from 2011-2020.
Keywords: The company's life cycle; accounting conservatism; economic decisions for investors